The Effect of Four Goal Football Drill on Passing Stopping Ability at Lubuk Bendahara Football Academy - Muhammad Alwi; Lolia Manurizal; Deri Putra (Jurnal Ilmu Keolahragaan, 2026)
This study aimed to analyze the effect of the four-goal football drill on improving the passing stopping ability of athletes at the Lubuk Bendahara Football Academy. The research method used was quantitative comparative with a pre-test and post-test design. The research sample consisted of 20 athletes (N=20) at the Lubuk Bendahara Football Academy. Data was collected through measuring passing stopping ability and analyzed using a dependent t-test after fulfilling the prerequisite tests for normality (Sig. Shapiro-Wilk pre-test 0.064; post-test 0.057) and homogeneity (Sig. Levene Statistic 0.768). The results showed a significant improvement in the athletes' ability after the training intervention; the average ability score surged from 4.85 in the pre-test to 6.70 in the post-test. A clear shift in categories was also observed: in the pre-test, the majority of athletes (95%) were in the Poor and Adequate categories; however, in the post-test, no athletes remained in the Poor category, and the majority were distributed into the Good (55%) and Adequate (45%) categories.The t-test result obtained a significance value of 0.000 (p<0.05), indicating that the null hypothesis was rejected and a significant effect exists. This study concludes that the four-goal football drill has a significant and positive effect on improving passing stopping ability, making it an effective and recommended method as it integrates technical, tactical, and cognitive aspects.